Prediction of Motor Myelopathic Severity in Patients with Cervical Spondylotic Myelopathy: How to Approach? - Ishrat Zahan, Kanij Fatema; Ul Alam, Mohammad Jahangir; Rahman, Md Asifur; Hasan, Md Motasimul; Rashed Mahmud; Hossain, Mohammad; Hossian, Mohammed Afzal (Bangladesh Journal of Neurosurgery, 2024)
Background: Cervical spondylotic myelopathy (CSM) is a challenging thing to diagnose as it has subtle symptoms and insidious onset. But, there is a relationship between signal intensity change of the spinal cord on MRI and cervical spondylotic myelopathy through which motor myelopathic severity in these patients can be predicted. Objective: The purpose of this study was to predict the motor myelopathic severity in patients with CSM with the help of magnetic resonance imaging (MRI). Methodology: This cross-sectional study was carried out in the Department of Neurosurgery at Banghabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from October, 2011 to March, 2013 for a period of one and half year. All patients who presented with cervical spondylotic myelopathy were included in this study. MRI of cervical spine was performed to all patients. Results: A total number of 36 patients with cervical spondylotic myelopathy were included in this study. Among the 36 study patients, all had normal intensity in the spinal cord on sagittal T1WI of MRI; however, there was variable intensity on sagittal T2WI of MRI. Low Nurick score was found in 24 (66.6%) patients who had type 0signal intensity on (T2WI) MRI. High Nurick score was found in 3 (8.3%) patients who had type 0 signal intensity on (T2WI) MRI. Low Nurick score was found in 2 (5.5%) patients who had type 1 signal intensity on (T2WI) MRI. High Nurick score was found in 6 (16.6%) patients who had type 1 signal intensity on (T2WI) MRI. Only 1 patient (2.7%) having high Nurick score (3- 5) had type-2 signal intensity on (T2WI) MRI (p<0.001). Conclusion: Prediction of motor myelopathic severity in patients with cervical spondylotic myelopathy can be done perfectly with the help of signal intensity change of the spinal cord on MRI which is very much helpful in patients’ management. Bang. J Neurosurgery 2023; 12(2): 71-75